Social Property: Utopia and Project - Pásara, Luis (1973)
In 1971, Peru introduced a new social property policy, sparking theoretical and political discourse regarding the establishment of this novel sector, often amid widespread ignorance. Subsequently, in 1973, the Social Property Law Project was unveiled, aiming to formalize this policy. This article seeks to scrutinize the proposed corporate social property regime outlined in this project. It delves into the definition of social property to extract its core characteristics, providing a framework for evaluating the project and identifying the economic and business transformations it entails.